Comparison of Fairness Conditions Comparison Study with Fuzzy C-Means and K-Means Methods - Lestari, Indah; Mahfud, Ashari; Zamroni, Edris; Sucipto, Sucipto; Latifah, Anisatul (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
The development of the character of fairness in teachers is influenced by the environmental conditions in which they grow and develop. This can be a factor that can influence the development of the fair character of teachers in the provinces of Central Java and Lampung. Therefore, this research aims to explore the fairness conditions among teachers in Central Java and Lampung provinces through a comparative study. This research involved 970 teachers spread across the islands of Java and Sumatra. The cluster sampling technique was used to take research subjects. The Comparison research method with The Fuzzy C-Means and K-Means Methods was carried out to obtain evidence regarding the fairness characteristics in teachers in Central Java and Lampung Provinces. The system testing results using the Silhouette coefficient method produced values ​​of 0.278 (Fuzzy C-Means) and 0.287 (K-Means), respectively. This value shows that K-Means outperforms Fuzzy C-Means because its value is close to 1. Furthermore, K-Means and Fuzzy C-Means obtain scores of 0.384 and 0.224, respectively, when evaluated with DBI. It can be concluded that Fuzzy C-means is superior to K-means because the lower DBI results show a good value close to zero. These results contribute to advocates of psychological assistance for teachers, that the characteristics of fairness conditions for teachers in the provinces of Lampung and Central Java are different. This analysis provides valuable insight into understanding the factors that influence teacher fairness in the two provinces and provides a basis for developing policies that are more effective in improving conditions of fairness in the education sector.